The Representation of Library Value in Extra-Institutional Evaluations of University Quality - Jackson, Brian (Canadian Journal of Higher Education, 2017)
The ways in which university quality assessments are developed reveal a great deal about value constructs surrounding higher education. Measures developed and consumed by external stakeholders, in particular, indicate which elements of academia are broadly perceived to be most reflective of quality. This paper examines the historical context of library quality assessment and reviews the literature related to how library value is framed in three forms of external evaluation: accreditation, university rankings, and student surveys. The review finds that the library’s contribution to university quality, when it is considered at all, continues to be measured in terms of collections, spaces, and expenditures, despite significant expansion of library services into non-traditional arenas, including teaching and research, scholarly communications, and data management and visualization. These findings are contrasted with the frequently invoked notion of the library as the heart of the university.